Journeying with God: spirituality and participation in faith related activities among Catholic youth in Whangarei : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Social Work in the Social Policy and Social Work Programme, School of Health and Social Services at Massey University - Dantis, Trudy Mary (Massey University, 2008)
This thesis examines the spirituality and participation in faith-based activities of young Catholics in Whangarei, New Zealand. Six youth aged 16-17 years have shared their experiences in several areas of Catholicism such as religious attendance, Catholic identity and Catholic faith, morals and values, peer group socialisation and religious commitment. Using a qualitative mixed-methodological approach with the underlying philosophical stance of interpretivism, the intent of the study is to discover ways in which these young Catholics integrate their faith into their daily lives and make meaning out of it. It also compares the religious beliefs and values of Catholic youth in Whangarei to those reported worldwide. The findings reveal many similar themes to those from international studies. Although all of the participants in this study possessed a distinct sense of ‘spirituality’ and being ‘Catholic’ was a very important part of their identity, not all of them seemed to consider it practical to live out their Catholic beliefs. Similarly, although they did not face any insurmountable challenges in practicing their faith in daily life, only a few of them had strong convictions about their faith and, like their peers in other countries, only a few could concretely list the core Catholic beliefs. Concepts of moralistic therapeutic deism were found to affect half the participants while nuances of moralistic relativism were also prevalent. Results also showed a growing disinterest in attending Mass, participating in the sacrament of Confession, leading an active prayer life, being a part of church youth activities and some difficulty in finding similar peer group support. Overall, the findings presented in this thesis suggested that the participants involved in the study could be separated into two groups on the basis of their differing spiritual levels and commitment to the Catholic faith The findings suggest a need for Catholic youth in Whangarei to be supported in their spiritual development in order to help them grow in their Catholic faith. Accordingly, the main recommendations are for community-based services such as providing a variety of youth programmes/groups to engage young people and finding ways to facilitate the secure engagement of youth in a dialogue about their faith and religion, in order to spiritually encourage, nourish and sustain them at whatever stage they might be at.
Keywords: Catholicism; Catholic identity; Religious commitment; Fields of Research::370000 Studies in Human Society::370200 Social Work::370299 Social work not elsewhere classified